Has Central Sensitization Become Independent of Nociceptive Input in Chronic Pancreatitis Patients Who Fail Thoracoscopic Splanchnicectomy?. Issue 6 (1st October 2011) - Bouwense, Stefan A.W.; Buscher, Hessel C.J.L.; van Goor, Harry; Wilder-Smith, Oliver H.G.
Abstract : Background and Objectives: Central sensitization due to visceral pancreatic nociceptive input may be important in chronic pancreatitis pain. We investigated whether bilateral thoracoscopic splanchnicectomy (BTS) to reduce nociceptive input in chronic pancreatitis patients (CPP) with poor pain control affects supraspinal and spinal sensitization. Methods: Seventeen CPP were studied preoperatively and 6 weeks after BTS. Pressure pain thresholds (PPT) were measured in clavicle and pancreatic dermatomes reflecting supraspinal and spinal central sensitization, respectively. Patients with increased PPT after BTS (hypoalgesic) were compared to those without (hyperalgesic) and PPT vs. pain numeric rating scale (NRS) changes compared. Results: After BTS, ten patients showed C5 PPT increases (hypoalgesic; median change 87 kPa), 7 patients had unaltered/lower PPT (hyperalgesic; −135 kPa). Preoperative pain NRS was similar between groups (4 vs. 5, P = 0.2). After BTS hypoalgesic group NRS was lower (1 vs. 6; P = 0.008) and NRS change greater (−2 vs. 0; P = 0.005). Whole group NRS and C5 PPT change correlated significantly and negatively ( r = 0.53; P < 0.05), but not for pancreatic PPT. Conclusions: Reduced supraspinal-but not spinal-central sensitization after BTS was associated with significantly reduced pain scores in a majority of CPP. A subgroup showed no reductions in supraspinal central sensitization after BTS, coupled to no significant pain NRS reduction. Our results suggest that a subgroup of CPP has altered pain processing that may be independent of ongoing peripheral nociceptive input, resulting in persisting pain despite BTS. If confirmed, these results indicate the importance of sensory testing for indications and management of pain treatments.